Organizational climate and employee engagement of micro-finance banks in South-East, Nigeria - Nwogwugwu Ngozi Ogechukwu; Ezimma Nnabuife; Patrick Okeke (Annals of Human Resource Management Research, 2022)
Purpose: The purpose of this study is to examine the relationship that exists between organizational climate and employee engagement in Microfinance Banks in South-East Nigeria. Research Methodology: The study adopted a Survey Research Design and the target population consisted of 3875 employees of all the Microfinance Banks in South-East Nigeria while the sample size was six hundred and eighty-seven (687) employees of the 31 selected banks. A simple random sampling technique was adopted by the study and a structured questionnaire was used in data collection and was analyzed by using Simple Regression Analysis at a 5% level of significance. Results: The findings indicated that there is a significant relationship existing between Career Development Climate and Employee Commitment in Microfinance Banks in South-East Nigeria (r = .961; R-Square = .923; p-value<.05) and that there is a significant relationship existing between Teamwork Climate and Absorption in Microfinance Banks in South-East Nigeria (r = .989; R-Square = .979; p-value<.05). Limitations: Most of the banks used in the study are state-based banks, thereby, limiting how the work would be generalized if it had used national-based microfinance banks. Contribution: this work contributed to the already existing body of knowledge in the area of organizational climate and employee engagement, but brought in empirical findings to back up the relationship between the variables in microfinance banks in Nigeria.